Evaluation of distribution and bioaccumulation of arsenic by ICP-MS in tilapia (oreochromis niloticus) cultivated in different environments - Oliveira, Luciano H. B. [UNESP]; Ferreira, Nathália S. [UNESP]; Oliveira, Andrea; Nogueira, Ana Rita A.; Gonzalez, Mario H. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2017)
The concentration of arsenic in tissues of tilapia was evaluated and an estimation of the risks associated with the consumption of this fish was done, taking into account the guidelines established by FAO/WHO. The inductively coupled plasma mass spectrometry (ICP-MS) technique in kinetic energy discrimination (KED) mode was employed and certified reference materials were analyzed with recoveries of 101, 110, and 80% from NIST 1640a (trace elements in water), NIST 1566b (oyster tissue), and DORM-3 (fish protein). In the consumable portion (the muscle fish tissue), the average concentration found was 0.030 ± 0.008 µg g-1, which is below the arsenic maximum level established by international regulatory agencies. The average concentration found in the viscera (stomach, gills, and liver) was 0.485 ± 0.225 µg g-1, concluding that the viscera had greater capacity for the bioaccumulation of arsenic. From this study was possible to monitor the arsenic element in different tilapia specimens evidencing its accumulation throughout the body of the fish.
Keywords: Arsenic; Bioaccumulation; Fish tissues; ICP-MS; KED mode